Histomorphological development and progression of gastric intramucosal papillary adenocarcinoma—a retrospective study - Wang, Yang-Kun; Zou, Xiong-Fei; Wang, Wen-Yi; Li, Ying-Ying; Zhong, Yan; Guo, Pei; Wang, Tao; Xu, Si-Liang; Wang, Su-Nan (Frontiers in Oncology, 2025)
ObjectiveThe aim of this study is to elucidate the developmental process, progression patterns, and histomorphological features of gastric-type intramucosal papillary adenocarcinoma.MethodsThis study employed a retrospective research method. Histological examination and immunohistochemical analyses were conducted on endoscopic biopsy samples and endoscopic submucosal dissection (ESD) specimens from 450 cases of superficial gastric epithelial lesions.ResultsAtrophic changes in gastric foveolar epithelium, resulting from infectious, chemical, autoimmune, or genetic factors, were associated with a sequential process of tumorigenesis in gastric intramucosal papillary adenocarcinoma. This process involved two phases of compensatory epithelial proliferation followed by three distinct stages of neoplastic transformation. The initial compensatory phase was characterized histologically by papillary hyperplasia of the gastric crypt epithelium. The second phase, representing transitional or dysregulated proliferation, was observed as gastric surface epithelial-type adenoma. The first neoplastic stage was identified as gastric-type low-grade intraepithelial neoplasia, followed by high-grade intraepithelial neoplasia, and culminating in the third stage as gastric-type intramucosal papillary adenocarcinoma. The progression of these stages was delineated based on histopathological features and immunophenotypic profiles.ConclusionRecognizing the histopathological and immunophenotypic features involved in the stepwise development of gastric-type papillary adenocarcinoma enhances the accuracy of clinical management and surveillance of neoplastic progression. This has significant implications for early intervention and prevention of gastric cancer progression.